The little bookstore on Heart Lake Lane - Robinson, Sarah (Heart Lake series, 2023)
"As chaotic as it can be, Rosie Dean loves her unruly life. But between raising twins alone, running her struggling bookshop, and secretly writing a parenting advice column, the single mom can't think about dating. At least that's what she tells herself . . . until her high school crush (and his incredible blue eyes) return to Heart Lake for the summer. Even though Evan has grown into a huge grump, he's still a super sexy one, and soon sparks begin to fly. Single dad and widower Evan Mills is used to hearing he's too serious. But with a grieving tween daughter to raise on his own, the graphic designer is just trying to stay strong for her. He hopes a few weeks at the lake will be the fresh start they both need. Evan never anticipated reconnecting with Rosie, or that she could make him feel whole again--if he'd give her the chance. Will one steamy summer with Rosie be long enough to melt Evan's heart?"--from Amazon.com.